Core/shell-structured upconversion nanophosphor and cadmium-free quantum-dot bilayer-based near-infrared photodetectors - Hong, A-Ra; Kim, Jungyoon; Kim, Su Yeon; Kim, Seong-Il; Lee, Kwangyeol; Jang, Ho Seong (OPTICAL SOC AMER, 2015)
The core/shell-structured upconversion nanophosphors (UCNPs) and Cd-free CuInS2/ZnS quantum dots (QDs) were synthesized via coprecipitation and hot-injection methods, respectively, and they were applied to near infrared (NIR) photodetectors. The beta-NaYF4:Yb; Er/beta-NaYF4 UCNPs emitted intense visible light peaking at 522, 542, and 656 nm via H-2(11/2), S-4(3/2), and F-4(9/2) -> I-4(15/2) transitions under excitation with 980 nm NIR light. The core/shell UCNPs showed 6.4 times higher emission intensity than core UCNPs. Charge carriers can be generated from CuInS2/ZnS QDs in the QD-UCNP mixture due to their broad absorption in the visible spectral region shorter than 600 nm. The photodetector devices were fabricated by spin-coating CuInS2/ZnS QDs on a SiO2/Si substrate with patterned gold electrodes followed by spin-coating UCNPs on the QD layer. The fabricated QD-UCNP-bilayer-based device showed a drastically increased photocurrent (128 mu A) compared with the QD-layer-based device under 980 nm NIR light illumination. Additionally, the fabricated device showed stable ON-OFF switching properties against on and off NIR light. (C) 2015 Optical Society of America
Keywords: NANOPARTICLES; NANOCRYSTALS; EMISSION; GREEN